A77 1726, the active metabolite of the anti‐rheumatoid arthritis drug leflunomide, inhibits influenza A virus replication in vitro and in vivo by inhibiting the activity of Janus kinases. Issue 8 (29th June 2020) - Wang, Jiongjiong; Sun, Jing; Hu, Jiao; Wang, Chengming; Prinz, Richard A.; Peng, Daxin; Liu, Xiufan; Xu, Xiulong
Abstract: The newly reassorted IAV subtypes from zoonotic reservoirs respond poorly to current vaccines and antiviral therapy. There is an unmet need in developing novel antiviral drugs for better control of IAV infection. The cellular factors that are crucial for virus replication have been sought as novel molecular targets for antiviral therapy. Recent studies have shown that Janus kinases (JAK), JAK1, and JAK2, play an important role in IAV replication. Leflunomide is an anti‐inflammatory drug primarily used for treating rheumatoid arthritis (RA). Prior studies suggest that A77 1726, the active metabolite of leflunomide, inhibits the activity of JAK1 and JAK3. Our current study aims to determine if A77 1726 can function as a JAK inhibitor to control IAV infection. Here, we report that A77 1726 inhibited the replication of three IAV subtypes（H5N1, H1N1, H9N2）in three cell types (chicken embryonic fibroblasts, A549, and MDCK). A77 1726 inhibited JAK1, JAK2, and STAT3 tyrosine phosphorylation. Similar observations were made with Ruxolitinib (Rux), a JAK‐specific inhibitor. JAK2 overexpression enhanced H5N1 virus replication and compromised the antiviral activity of A77 1726. Leflunomide inhibited virus replication in the lungs of IAV‐infected mice, alleviated their body weight loss, and prolonged their survival. Our study demonstrates for the first time the ability of A77 1726 to inhibit JAK2 activity and suggests that inhibition of JAK activity contributes to its antiviral activity.